Taify Pomegranate Juice (TPJ) Abrogates Acrylamide-Induced Oxidative Stress Through the Regulation of Antioxidant Activity, Inflammation, and Apoptosis-Associated Genes - El-Shehawi, Ahmed M.; Sayed, Samy; Hassan, Mohamed M.; Al-Otaibi, Saad; Althobaiti, Fayez; Elseehy, Mona M.; Soliman, Mohamed (Frontiers in Veterinary Science, 2022)
Acrylamide (ACR) had various effects on biological systems including oxidative stress and its associated metabolic disorders. Previous research reported that plants growing at high altitude have different profile of antioxidants. In the current report, the Taify pomegranate juice (TPJ) of the Taify pomegranate growing at Taif region (high altitude), Saudi Arabia was investigated for its protective activity from the ACR-induced oxidative stress. Rats were treated with ACR, TPJ, or TPJ+ACR and various assays including blood chemistry, liver function biomarkers, gene expression of endogenous antioxidant enzymes, oxidative stress regulatory genes, inflammation biomarkers, and apoptosis were estimated using biochemical, real time PCR, histopathological and immunohistochemical analysis. The TPJ showed protective function of ACR-induced alteration of AST, ALT, GGT, urea, total proteins, albumin, MDA, and NO. It also increased the level of the endogenous antioxidative enzymes including SOD, catalase, and GSH. It showed anti-inflammatory activity by enhancing the TNF-α, IL-6 secretion and the reduction of IL-10 levels. At the gene expression level, TPJ upregulated the expression of endogenous antioxidant genes (SOD and catalase), and upregulated the expression of antioxidant regulating genes Nrf2 and HO-1, downgreulated the expression of inflammatory genes TGF-β1, COX2, the apoptotic gene caspase-3, and upregulated the expression of apoptotic gene Bcl2. At the histological level, TPJ showed protective effect from the ACR-induced hepatic histological damage. Results of this study conclude that TPJ had protective effect from ACR-induced oxidative stress and its associated metabolic alterations through its antioxidant and anti-inflammatory activities.